IMPACT OF ANODE-CATHODE DISTANCE VARIATIONS ON NICKEL ELECTROPLATING OF AISI 1020 STEEL: HARDNESS AND CORROSION RATE ANALYSIS - Nereus Tugur Redationo; Mannuel, Carlos Yoga; Murdiyanto, Danang (Universitas Katolik Widya Karya Malang, 2024)
Nickel electroplating on AISI 1020 steel is expected to increase hardness and enhance aesthetic appearance. Nickel plating on AISI 1020 steel is also anticipated to protect the steel surface and reduce the rate of corrosion. In the nickel electroplating process, researchers studied variations in the anode-cathode distance (5 cm, 10 cm, and 15 cm) and the use of an aerator. Data from Vickers hardness tests, corrosion rate tests, and microstructure photos were used as the basis for analyzing corrosion rates. The corrosion rate value without the aerator at an anode-cathode distance of 15 cm is 0.034 mm/year, at 10 cm is 0.019 mm/year, and at 5 cm is 0.015 mm/year. With the use of an aerator, the corrosion rate at an anode-cathode distance of 5 cm is 0.022 mm/year, at 10 cm is 0.011 mm/year, and at 15 cm is 0.008 mm/year. The Vickers hardness values without the aerator for these distances were 337.3 VHN, 190 VHN, and 286 VHN, respectively, while with the aerator, the hardness values were 301.67 VHN, 200.33 VHN, and 339 VHN.